2014
DOI: 10.1002/jbm.b.33206
|View full text |Cite
|
Sign up to set email alerts
|

In vitro biocompatibility and cellular interactions of a chitosan/dextran‐based hydrogel for postsurgical adhesion prevention

Abstract: In this paper, we report the in vitro biocompatibility and cellular interactions of a chitosan/dextran-based (CD) hydrogel and its components as determined by mutagenicity, cytotoxicity, cytokine/chemokine response, and wound healing assays. The CD hydrogel, developed for postsurgical adhesion prevention in ear, nose, and throat surgeries, was shown by previously published experiments in animal and human trials to be effective. The hydrogel was synthesized from the reaction between succinyl chitosan (SC) and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…In our study, the low number of positive wells and the lack of a dose‐response, either in the presence or absence of S9 fractions suggest that the HG and its metabolites lack mutagenic activity at the concentrations tested. Negative mutagenicity results have been also reported for an HG composed by succinyl chitosan and aldehyde dextran (0.5‐8 mg/mL) as assessed by the Ames test (Aziz et al, ).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In our study, the low number of positive wells and the lack of a dose‐response, either in the presence or absence of S9 fractions suggest that the HG and its metabolites lack mutagenic activity at the concentrations tested. Negative mutagenicity results have been also reported for an HG composed by succinyl chitosan and aldehyde dextran (0.5‐8 mg/mL) as assessed by the Ames test (Aziz et al, ).…”
Section: Discussionmentioning
confidence: 92%
“…In fibroblasts, DA displayed a strong decrease of cell viability at conditions greater than 5 mg/mL. After the combination between DA and succinyl chitosan to obtain the dextran‐based hydrogel, this showed a strong and immediate cytotoxic effect in epithelial cells, in contrast to the macrophage and fibroblast cells, which exhibited a more moderate response with a ~40% overall reduction in cell viability (Aziz et al, ). The cytotoxic effect of aldehydes is most likely due to their reaction with amino acids of the culture medium and free amines in the cell, causing a negative effect on cellular growth (Hyon et al, ; Rousseau & Gagnieu, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence optical imaging was chosen due to its sensitivity to visualize compounds at surgical concentrations as well as provide high signal to noise ratios with low background. 29 Imaging using NIR-sensitive probes conjugated to hydrogels have been used successfully to target cancer cells, 30 35 The bioactivity of DA combined with the barrier function of the hydrogel was thought to explain the anti-adhesion mechanism of the CD hydrogel. In order to develop the CD hydrogel as a post-operative adhesion preventing adjunct for surgeries other than ESS, a lower oxidized and less cytotoxic DA, DA-25, was developed 20 and mixed with SC to create the CD-25 formulation.…”
Section: 13mentioning
confidence: 99%
“…They showed that co-encapsulation of several GFs in macroporous scaffolds of dextran and simultaneous release of them can be dramatically enhance the size and number of newly-formed functional vessels in in vivo conditions. Furthermore, dextran NPs themselves and dextran grafted with different biomaterials such as 2-hydroxyethyl methacrylate (HEMA), poly-l-lysine, chitosan, pullulan, gelatin, PEG derivatives and poly(anhydride) have been used as tissue bioadhesives in tissue regeneration [25][26][27].…”
Section: Tissue Engineering By Dextranmentioning
confidence: 99%